Model Pengelolaan Sampah Plastik Dalam Mendukung Green Economy - Terry Sugihardi; Alysa Dwi Suci; Kesha Aprilisa Putri; Raffi Pratama Septiadi; Muhammad Rafli Fahru Rois; Rafli Nurul Arifin (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2026)
The problem of plastic waste has become an increasingly complex environmental issue due to the rising use of plastic, which is not balanced by effective management. Plastic waste, which is difficult to decompose, has a negative impact on the environment and threatens the sustainability of ecosystems. Therefore, a management approach is needed that not only focuses on waste reduction but is also capable of creating added value through the concept of a sustainable economy. This study aims to analyze plastic waste management models in support of green economy implementation. The method used is a qualitative approach involving literature review (library research), utilizing secondary data obtained from scientific articles in the Google Scholar and SINTA databases over the past five years. The descriptive-comparative analysis technique was used to identify patterns, trends, and innovations in plastic waste management. The results indicate that plastic waste management is evolving through the integration of technology-based innovations and community participation. The technological approach plays a role in improving processing efficiency and reducing waste volume, while the community-based approach is effective in raising awareness and fostering behavioral change. In addition, plastic waste management also contributes to promoting the implementation of a circular economy as part of the principles of a green economy. The theoretical implications of this study confirm that innovations in plastic waste management play a crucial role in supporting sustainable development through resource optimization and the reduction of environmental impacts.